The vertebrate fauna of the Upper Permian of Niger—X. The mandible of the captorhinid reptile Moradisaurus grandis. Issue 6 (2nd November 2018) - Modesto, Sean P.; Richards, Courtney D.; Ide, Oumarou; Sidor, Christian A.
ABSTRACT: Recent field work in the upper Permian Moradi Formation of Niger has yielded new material of the late-occurring and largest moradisaurine captorhinid, Moradisaurus grandis . The material includes two right hemimandibles, which represent individuals that are slightly smaller than the holotype. The smaller size of these mandibles, together with evidence in the form of tooth replacement, strongly suggest that the new material is ontogenetically younger than the holotype. The available evidence implies that tooth rows were added during growth in M. grandis . The mandible of M . grandis is distinguished from other moradisaurines in the extreme lingual extension of the tooth plate, which forms a dental shelf or plateau that supports the three lingual-most rows of teeth. In addition, a mentomeckelian bone is preserved, the first to be reported in a Paleozoic reptile. In contrast to the conspicuous wear documented on the teeth of certain other moradisaurines, wear facets are not observed on the teeth of the M . grandis specimens described here. The absence of tooth wear is surprising because the articular morphology of M . grandis is virtually identical to, albeit slightly larger than, that of Labidosaurikos meachami, for which propalinal jaw movement was first inferred in a moradisaurine. A phylogenetic analysis incorporating the new anatomical information confirms the hypothesis that M . grandis forms a clade with Rothianiscus multidontus and Gansurhinus qingtoushanensis within Moradisaurinae, and positions Captorhinikos chozaensis as the basal-most member of the subfamily.